Update on biomaterials for prevention of epidural adhesion after lumbar laminectomy - Huailan Wang; Wenjia Sun; Dongliang Fu; Yueliang Shen; Ying-ying Chen; Lin-lin Wang (Journal of Orthopaedic Translation, 2018)
Summary: Lumbar laminectomy often results in failed back surgery syndrome. Most scholars support the three-dimensional theory of adhesion: Fibrosis surrounding the epidural tissues is based on the injured sacrospinalis behind, fibrous rings and posterior longitudinal ligaments. Approaches including using the minimally invasive technique, drugs, biomaterial and nonbiomaterial barriers to prevent the postoperative epidural adhesion were intensively investigated. Nevertheless, the results are far from satisfactory. Our review is based on various implant biomaterials that are used in clinical applications or are under study. We show the advantages and disadvantages of each method. The summary will help us to figure out ideas towards new techniques.The translational potential of this article: This review summarises recent biomaterials-related clinical and basic research that focuses on prevention of epidural adhesion after lumbar laminectomy. We also propose a novel possible translational method where a soft scaffold acts as a physical barrier in the early stage, engineered adipose tissue acts as a biobarrier in the later stage in the application of biomaterials and adipose-derived mesenchymal stem cells are used for prevention of epidural adhesion. Keywords: Adhesion, Biomaterials, Fibrosis, Implant, Laminectomy